The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/agronomy11050848
|View full text |Cite
|
Sign up to set email alerts
|

Change of Physiological Properties and Ion Distribution by Synergistic Effect of Ca2+ and Grafting under Salt Stress on Cucumber Seedlings

Abstract: Salinization is an important soil environmental problem, which severely restricts the sustainable production of cucumbers. Therefore, how to improve the salt tolerance of cucumbers is a global problem. Grafting improves the resistance of crops, and calcium ion (Ca2+) weakens the permeability of the plasma membrane. In this paper, grafting cucumber with NaCl-free treatment was the control treatment (CK). Under salt stress, grafting combined different concentrations of CaCl2 and non-grafted (NG) were considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Grafting (an eco-friendly surgical horticulture technique) of cucumber on suitable rootstock improves the crop growth and productivity by increasing the morphological (root tip, diameters, and length), physiological (photosynthetic rate, water use efficiency) and biochemical (SOD, CAT and POX) indices 21 , 22 . Grafting helps crop plants to tolerate salt stress by replacing the sensitive crop roots with tolerant genotypes species, and decreasing the production losses 23 via reducing the Na + and enhancing the K + uptake through the leaves and stems. Thus, maintains appropriate K + : Na + .…”
Section: Introductionmentioning
confidence: 99%
“…Grafting (an eco-friendly surgical horticulture technique) of cucumber on suitable rootstock improves the crop growth and productivity by increasing the morphological (root tip, diameters, and length), physiological (photosynthetic rate, water use efficiency) and biochemical (SOD, CAT and POX) indices 21 , 22 . Grafting helps crop plants to tolerate salt stress by replacing the sensitive crop roots with tolerant genotypes species, and decreasing the production losses 23 via reducing the Na + and enhancing the K + uptake through the leaves and stems. Thus, maintains appropriate K + : Na + .…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ is an important nutrient and a signaling molecule that regulates plant growth and development [28]. Previous studies have demonstrated that treatment with 10 mmol•L −1 CaCl 2 significantly increases the biomass of Zoysia japonica and cucumber [29,30]. Moreover, the foliar application of Ca 2+ promotes peanut growth and improves the quality of sweet cherries [31][32][33].…”
Section: Discussion 41 There Is An Optimum Calcium Concentration For ...mentioning
confidence: 99%
“…Tuna et al (2007) found that the application of exogenous calcium improved the inhibition of plant growth by salt stress. The addition of calcium has been shown effective in promoting the growth and yield of tomato, soybean and cucumber under salt stress (Navarro et al, 2000;Elkelish et al, 2019;Wang et al, 2021). The leaf area, biomass and roots of salt-tolerant and saltsensitive rice have been shown to increase significantly with increasing exogenous calcium (Cha-um et al, 2012).…”
Section: Exogenous Calcium Regulates the Growth Of Salix Matsudana Se...mentioning
confidence: 99%